Filosofizzazione del cristianesimo - Magris, Aldo (Verbum Vitae, 2021)
Whereas all major aspects of the Hellenic civilization faded away at the triumph of the Christian religion, only Greek philosophy remained, and found some original developments inside the new cultural environment. Therefore, we should speak rather of philosophization than of hellenization of Christianity. Many earlier Christian authors were indeed hostile towards philosophy, yet Justin’s, Clement’s and Origen’s line prevailed, saying it could provide a propedeutics to the understanding of faith, although not as a whole but specifically in its Platonic and Aristotelian tradition. The Church Fathers gathered from the repertoire of these sources most notions and topics useful for two aims: firstly, the assumption of the free will supporting ethics, and the demonstration of the divine providence as a pivot for theodicy; secondly, the refutation of pagan idolatry and contemporary heresies. Above all, against the Manicheans they made wide use of the key concepts drawn from the Aristotelian ontology. The philosophization has become an integral part of Christian identity and vision.